Phosphorus‐containing Salen‐Ni metal complexes enhancing the flame retardancy and smoke suppression of epoxy resin composites. Issue 21 (21st November 2019) - Cui, Jinfeng; Zhang, Yabin; Wang, Lurong; Liu, He; Wang, Niannian; Yang, Baoping; Guo, Junhong; Tian, Li
ABSTRACT: Two novel Salen‐DPCPs metal complexes (Salen‐DPCP‐1 and Salen‐DPCP‐2), containing both Salen‐Schiff base (Salen), phenyl phosphate structures (DPCP) and nickel component, were prepared to reduce fire hazards of epoxy resin (EP). The results showed that 5 wt % addition of Salen‐DPCP‐1 brought a higher flame‐retardant efficiency to the EP, where the V‐0 rating in UL‐94 burning test and 31.5% of limiting oxygen index (LOI) were achieved. Meanwhile, total heat release, total smoke production, and total CO yield dramatically decreased by 28.1, 23.6, and 21.4%. In addition, these results basically reappeared when Salen‐DPCP‐2 were introduced into EP to obtain Salen‐DPCP‐2/EP composites. Chemical structure and morphology characterization of the carbon residue confirmed that Salen‐DPCPs improved the catalytic charring ability and the noncombustible gas releasing ability by the Fourier transform infrared, X‐ray photoelectron spectroscopy, and Scanning electron microscopy technology. Therefore, it is an efficient strategy to develop novel Salen composites modified by flame‐retardant groups to improve the fire rating of polymers. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48734. Abstract :